Paternal origin of the de novo deleted chromosome 4 in Wolf-Hirschhorn syndrome. Issue 1 (January 1992) - Tupler, R; Bortotto, L; Bühler, E M; Alkan, M; Malik, N J; Bösch-Al Jadooa, N; Memo, L; Maraschio, P
Abstract : The parental origin of the de novo deleted chromosome 4 was studied in five cases of Wolf-Hirschhorn syndrome using polymorphic probes mapping in the 4p16.3 region. In all the patients the deleted chromosome was found to be of paternal origin and these results, together with similar ones obtained by another group, make the preferential paternal origin of the de novo chromosome 4 deletion highly significant.